KURASSAKI:BENTUK DAN STRATEGI TANGGUNGJAWAB TERHADAP SAMPAH SISWA MIN 2 MAGETAN - Erlinda Putriana; Fuad Fitriawan; Ais Rosyidah (BASICA: Journal of Arts and Science in Primary Education, 2021)
Garbage is a problem that always appears in various media, humans as the main actors sometimes feel that they have nothing to do with the problem of waste. Various kinds of waste are recognized or not as the cause is human, there are organic waste that can still be used or can be decomposed, there are inorganic waste such as domestic liquid waste, industrial waste, heavy metal waste to toxic waste. MIN 2 magetan's concern with the problem of waste has yielded results. The Kurassaki program, which was launched for more than 2 years, can be carried out by all school components, starting from students, teachers and other personnel. Lessons learned from the Tangerang City Government as a pioneer, one of which has implemented it in the province of East Java is MIN 2 Magetan.